Usability of open source software within Malaysia business environment / Siti Sarah Hasamdin - Hasamdin, Siti Sarah (2002)
This study was carried out to find out level of acceptance of Open Source Software and the pattern of its usage among companies in Malaysia especially in Subang Jaya. For this purpose, the established content area usage of open source software in companies in Malaysia were compared with the usage of open source software in developed countries such as United Kingdom. This study also covered the impact of open source software to the society as well as to the government, educational and corporate sectors. In addition, organization's, government's and individual's perception on open source movement were surveyed. The study was divided into three stages. The first stage was devoted to collecting and analysing materials such as article in the newspapers, magazines and Internet. The second stage was acquiring information from the Open Source Software developers via emails to get the overview of the scenario of Open Source Software in Malaysia. The final stage was, getting response from companies as the research sample that is located in Subang Jaya through interviews and questionnaires. The findings indicated that this open source movement has awakened many people, whereas the proprietary software company feels like this movement is a threat to the industry itself. Apart of this, findings also shows that the open source software is now more acceptable in Malaysia compared to the early years of it's existence. The findings imply that the open source software still need to improve in the interaction with human, as it is still new and people need time to be comfortable using them.